EFFECTS OF ALTERNATING SHIFT SCHEDULES ON NURSES WORKING IN SAIDU GROUP OF TEACHING HOSPITALS (SGTH) IN SWAT, PAKISTAN (The Research of Medical Science Review, 2025)
The research study was conducted in Saidu Group of Teaching Hospitals (SGTH), Saidu Sharif, Swat District, Khyber Pakhtunkhwa, Pakistan. The major area of this research is to discover the effects of alternating shift schedules on the health and psycho-social aspects of nurses working in SGT hospitals. The purpose of the study is to appraise the degree of biological, psychological societal hazards forced on nurses by alternating shift schedules. Currently most of Pakistani nurses, offering their duties either in three shift basis or standard 12 hours shift in different hospitals in the country. The hypothesis is that long lasting and alternating shift schedules affect the nursing personnel both physiologically and psychosocially.The SGT hospitals were marked to collect extra managerial information concerning alternating shift including night shift because it has parallel managerial processes to any private hospital in the province. 2 set of nurses were engaged in the study, Daytime shift and nighttime shift nurses. Daytime shift nurses were engaged as a set that is also allocated to work on nighttime shift when there is a need present for them, functioning as an alternating staff for a certain period. Seventy-two nurses contributed as respondents to a questionnaire.The results of this research study reported that alternating shift schedules cause psychological, communal and biological problems to nurses, particularly those doing the rapid alternations. Nurses articulated added complaints about alternating or night shift as in comparison to daytime shift. Few nurses give preference to do the alternative shift. The majority of those prefer night shift due to social problems such as transport.